2021
DOI: 10.1177/17562864211049208
|View full text |Cite
|
Sign up to set email alerts
|

Secondary mechanisms of injury and viable pathophysiological targets in intracerebral hemorrhage

Abstract: Intracerebral hemorrhage (ICH) can be divided into a primary and secondary phase. In the primary phase, hematoma volume is evaluated and therapies are focused on reducing hematoma expansion. In the secondary, neuroprotective phase, complex systemic inflammatory cascades, direct cellular toxicity, and blood-brain barrier disruption can result in worsening perihematomal edema that can adversely affect functional outcome. To date, all major randomized phase 3 trials for ICH have targeted primary phase hematoma vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 62 publications
(214 reference statements)
0
31
0
Order By: Relevance
“…Cilengitide trifluoroacetate, an inhibitor of integrin αVβ5 [ 24 ], was shown to significantly decrease the expression of p-AMPK and reversed the beneficial effects of irisin on neurobehavior deficits and neuroinflammation after ICH. In addition, our data showed that dorsomorphin, a selective phosphorylated AMPK inhibitor [ 3 ] significantly reversed the anti-inflammatory, anti-apoptotic effects and neurobehavior protection of irisin post-treatment. Collectively, these data suggested that irisin post-treatment alleviated neuroinflammation possibly through the integrin αVβ5/AMPK signaling pathway after ICH.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Cilengitide trifluoroacetate, an inhibitor of integrin αVβ5 [ 24 ], was shown to significantly decrease the expression of p-AMPK and reversed the beneficial effects of irisin on neurobehavior deficits and neuroinflammation after ICH. In addition, our data showed that dorsomorphin, a selective phosphorylated AMPK inhibitor [ 3 ] significantly reversed the anti-inflammatory, anti-apoptotic effects and neurobehavior protection of irisin post-treatment. Collectively, these data suggested that irisin post-treatment alleviated neuroinflammation possibly through the integrin αVβ5/AMPK signaling pathway after ICH.…”
Section: Discussionmentioning
confidence: 87%
“…Intracerebral hemorrhage (ICH) is a severe fatal subtype of stroke accounting for approximately 10 to 15% of all stroke patients, with high rates of mortality and morbidity [ 1 , 2 ]. The formation of a huge hematoma and mechanical compression to surrounding brain tissues after sudden rupture of cerebral blood vessels results in intracranial hypertension and neurological deterioration, which is regarded as the primary brain injury [ 3 ]. However, surgical intervention of the hematoma in ICH patients used in clinical practice rarely improves the neurological prognosis of patients [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thrombin activation after ICH implies the vasculogenic edema formation associated with the destruction of endothelial cells and the BBB ( Wilkinson et al, 2018 ). Perihematomal edema (PHE), associated with a worse prognosis, has been recognized as an evident marker of SBI after ICH and a likely therapeutic pathophysiological target for attenuating SBI ( Brouwers and Greenberg, 2013 ; Bautista et al, 2021 ; Chen et al, 2021 ). Furthermore, it was displayed that intracranial hematoma expands to further and adjacent brain tissues through perivascular spaces, white matter tracts, and their perineurium ( Yin et al, 2013 ; Fu et al, 2021 ), particularly if ICH is combined with an intraventricular hemorrhage ( Bosche et al, 2020 ).…”
Section: Pathological Changes After Intracerebral Hemorrhagementioning
confidence: 99%
“…A recent review summarizes all ion channels and transporters which can have a proposed role in mediating cerebral edema in acute ischemic stroke and TBI [211]. Moreover, in intracerebral hemorrhage, the potential targets for reducing secondary injury mechanisms were summarized [234]. These previous reviews also highlight the need for a good target and numerous attempts to find a suitable target.…”
Section: The Importance Of Trpm4 In Central Nervous System (Cns) Pathophysiologymentioning
confidence: 99%